2019
DOI: 10.1021/acs.jpcc.9b04713
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Interactions of Amino Acids and Nucleic Acid Bases with Bare Black Phosphorene Monolayer Mediated by Coadsorbed Species

Abstract: In this paper, we characterize amino acids and nucleic acid bases (nucleobases), such as glutamine, histidine, tyrosine, adenine, guanine, cytosine, and thymine, and examine their interaction with bare, as well as with gold cluster and Ti adatom covered, black phosphorene (α-P) monolayers using density functional theory. The binding of these amino acids and nucleobases to the bare α-P monolayer is realized generally through weak van der Waals interaction and comprises only a small amount of charge exchange. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Song et al [50] showed that the Au atom can increase the binding energy between the aromatic amino acids such as phenylalanine (Phe), tyrosine (Tyr), and tryptophan (Trp) on MoS 2 monolayer. Additionally, Gorkan et al [17] and Kadioglu et al [51] reported that interactions of amino acids and nucleobases with Au clusters supported blue and black phosphorene, respectively.…”
Section: Binding Mechanism Of Li/au-doped Silicene and Germanene Monomentioning
confidence: 99%
“…Song et al [50] showed that the Au atom can increase the binding energy between the aromatic amino acids such as phenylalanine (Phe), tyrosine (Tyr), and tryptophan (Trp) on MoS 2 monolayer. Additionally, Gorkan et al [17] and Kadioglu et al [51] reported that interactions of amino acids and nucleobases with Au clusters supported blue and black phosphorene, respectively.…”
Section: Binding Mechanism Of Li/au-doped Silicene and Germanene Monomentioning
confidence: 99%
“…In addition, by exploring the energy decomposition (see Table 1 and Table 2 ), the binding energy is split into destabilized (positive) and minor deformation energies related to G, A, C, T, and U adsorption states, respectively, and stabilized (negative) with predominant interaction energies between nucleobases with oxygen and sulfur layer sides of the Janus MoOS surfaces (vdW interactions). In addition, the reason that G exhibits the largest binding energy or smallest interaction energy in both sides (O layer or S layer) of the Janus MoOS monolayer and other biomaterials [ 7 , 18 , 45 , 48 , 49 , 50 , 51 , 52 ], is relatively associated with high polarizability prior to other nucleobases [ 50 , 52 , 53 ]. This trend is more encouraging by the charge density distributions and molecular interactions (in the supplementary materials see Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, bulk gold, which is known to be as inactive as the noble gases, shows a catalytic effect when it is reduced to nanosizes. 3,4 Especially after the discovery of graphene, two-dimensional (2D) materials have been studied for a variety of fields, such as energy harvesting, 1,5-7 battery applications, 8,9 medical applications, [10][11][12][13] wearable electronics, 14,15 etc. New requirements emerging in next-generation technologies lead scientists to search for new materials.…”
Section: Introductionmentioning
confidence: 99%